Новые находки видов рода Peridiscophrya (Ciliophora, Suctorea) и замечания по таксономии рода - Жариков, В.В.; Быкова, С.В.; Довгаль, И.В. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
В двух водоемах в бассейне р. Волга были обнаружены суктории-дискофриины Peridiscophrya florea и P. crassipes. В статье приводятся данные по экологии, уточненные диагнозы данных видов, а также типового вида рода Peridiscophrya — P. japonica. На базе новых данных по морфологии видов переописан род Peridiscophrya Nozawa, 1938. Discophryin suctorian ciliates Peridiscophrya florea and P. crassipes were found in periphyton of two small lakes from Volga River basin. The data on the species ecology and refined diagnoses both observed species and the type species of the genus Peridiscophrya (P. japonica) are given in the article. On the strength of new data on species morphology the genus Peridiscophrya Nozawa, 1938 have been redescribed.